2004
DOI: 10.1152/jn.01146.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Neural Architectures Onto Acoustic Features of Birdsong

Abstract: The motor pathway responsible for the complex vocalizations of songbirds has been extensively characterized, both in terms of intrinsic and synaptic physiology in vitro and in terms of the spatiotemporal patterns of neural activity in vivo. However, the relationship between the neural architecture of the song motor pathway and the acoustic features of birdsong is not well understood. Using a computational model of the song motor pathway and the songbird vocal organ, we investigate the relationship between song… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…It will initiate, in a manner not addressed here, sparse bursts of high frequency ͑613± 210 Hz͒ spikes projecting to the RA and area X. The RA processes these sparse bursts in a fashion we have explored elsewhere [11], while the AFP relays these sparse bursts to the RA producing a time delay ⌬T whose biophysical origin we will explore.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…It will initiate, in a manner not addressed here, sparse bursts of high frequency ͑613± 210 Hz͒ spikes projecting to the RA and area X. The RA processes these sparse bursts in a fashion we have explored elsewhere [11], while the AFP relays these sparse bursts to the RA producing a time delay ⌬T whose biophysical origin we will explore.…”
Section: Introductionmentioning
confidence: 95%
“…2 where we have two PNs and one IN to represent the nucleus. A larger model with order of 100 PNs projecting to muscle control and 100 PNs projecting to respiration control along with 3-5 PNs in each population would be required to represent the way the RA nucleus distributes command signals from many HVc RA projecting neurons and determines details of syllables in each motif of a song [11]. Our focus here is in the mechanisms which control the synaptic plasticity at the HVc→ RA junctions, and what we reveal in our calculations will be operating at each such junction in a larger model.…”
Section: A Ra Structurementioning
confidence: 99%
See 2 more Smart Citations
“…experimentalists [6,27] and assumed in several theoretical studies [28,29,30]. In a recent experiment [26], calcium imaging and timing studies of intracellular recordings have suggested the existence of synfire chains in the visual cortices of mice and cats but no similar imaging study has yet been carried out for songbirds.…”
Section: A a Homogeneous 1d Chain Of Excitatory Neuronsmentioning
confidence: 99%